Student's Socioaffective Strategy In Reading - Vijaya, Rosyidah Jayanti (Journal of English and Education (JEE), 2012)
Informatics grows fast along with articles related to it and the students of STMIK AMIKOM need to have the ability to read comprehensively to deal with her study and work place. This case study is aimed to explore and find the pattern of student's socioaffective strategies in reading and how they are applied. As the socioaffective strategy found, it will be easier for the teachers to provide English reading materials that suit their strategy preferences, more enjoyable for the students, and raise students' awareness of socioaffective strategy. Hopefully, it will lead students to become autonomous in reading, foster their good adjustment in study and work place, bring a broader awareness of socioaffective strategy in reading, and invites further research related to this strategy. A preliminary observation was taken to choose one Information System student of semester 3, who had just experienced reading class, as this project participant. Data were collected through interviews with 16 indicators of socioaffective strategy. Steps of data analysis and data coding system were also prepared to make the research and data analysis easier. Result shows that the participant applied 13 of 16 socioaffective strategies. A good self-confidence and maturity make her be able to encourage herself to be sure of what she does. Student's taking emotional temperature strategy through taking risk wisely and cooperating with peers -as part of cooperating with others' strategy- seemed to be student's best preferences among others.Keywords: strategy, socioaffective strategy, and reading